Multi-walled carbon nanotube and nanosilica chemically modified carbon paste electrodes for the determination of mercury(ii) in polluted water samples. Issue 15 (7th August 2015) - Ali, Tamer Awad; Mohamed, Gehad G.
<x xml:space="preserve">Abstract</x> Novel carbon paste ion selective electrodes based on the 1, 4-bis(6-bromohexyloxy)benzene (BHOB) ionophore were constructed in order to determine the Hg(ii) ion concentration.